Analisis Perilaku Sanitasi Lingkungan Masyarakat Kelurahan Bagan Deli Kecamatan Medan Belawan - Nanda, Meutia; Erwina, Bella Putri; Rahman, Aulia Arief; Zahra, Mauliza; Maziaturrahman, Maziaturrahman; Purwadi, Puspa Ofri Anti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Efforts to improve the health of the environment and improve healthy living behaviors for the community have great leverage in improving the health status of the community. The problem of latrines and community waste disposal is very troubling. Environmental sanitation is a human effort to maintain health by creating a healthy living environment. This study aims to determine the description of the environmental sanitation behavior of the Bagan Deli village community, Medan Belawan sub-district. The type of research used is quantitative research with descriptive methods. The research population is the community in Bagan Deli Village, neighborhood V. The sample in this study amounted to 82 using the Slovin formula. set a margin of error of 5% (0.05). Data collection was obtained through observation and interviews with members of the public using questionnaires. Respondents with the condition that there are no latrine facilities are 39 people (47.6%), have suggestions but do not meet the requirements (30.5%), and 18 people (22%) have facilities that meet the requirements. A total of 74 people (90.2%) have a bathroom in the house. Sources of clean water come from drilled wells (78%), and 22% have PDAM water sources. the availability of landfills, so that people dispose of waste and garbage in ditches that directly lead to the sea. This causes the problem of itchy skin disease caused by the garbage rising during high tide. Keywords: Environmental Sanitation, Latrine, Clean Water, and Public Health